Respons Superovulasi Sapi Peranakan Ongole terhadap Penyuntikan Tunggal Follicle Stimulating Hormone ke dalam Ruang Epidural (SUPEROVULATION RESPONSES IN ONGOLE CATTLE CROSSBREED TREATED WITH A SINGLE EPIDURAL INJECTION OF FOLLICLE STIMULATING HORMONE) - Imron, Muhammad; Supriatna, Iman; ., Amrozi; Setiadi, Mohamad Agus (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
Super-ovulation is conventionally performed by injection of FSH twice daily for four days. Thistreatment needs frequent attention by farm-personnel and relatively increases the possibility of failuresdue to mishandling and errors in administration of the treatment. This study was conducted to evaluatethe responses of superovulation trough a single injection of FSH into epidural space in ongole cattlecrossbreed. In Experiment 1, a combination of single dose injection of FSH was applied into epidural spaceplus intramuscular (epi+i.m group) compared to the group of intramuscular injection of FSH, which wastreated twice daily for four days (intramuscular group), using equal total dose of FSH 400 mg. Superovulationresponse of epi+im group (n=4) was not significantly different compared with intramusculargroup (n=4). In experiment 2, it compared two treatmentof FSH in different concentration(280 mg versus160 mg) in a single dose applied into epidural space. Data of Epi+im group from experiment 1 was used ascontrol. Group of 280 mg FSH (n=4) resulted total collection of ova/embryo and transferable embryos(9,00+2,65 and 3,33+2,52 respectively) was significantly different compared to the 160 mg group (n=4)(which were 2,00+1,26 and 0,00) P <0,05, although they werenot significantly different compared to thecontrol (9,33+5,68 and 3,67+3,21). In conclusion, injection of a single dose of FSH at 280 mg into epiduralspace result in a comparable transferable embryo which similar to the conventional method that appliedintramuscular injection of FSH twice daily for four days.
Keywords: FSH single injection; epidural space; super-ovulation; PO cattle